臺灣與中國大陸國小教師專業發展政策與實施現況之分析研究 An Analysis Study on Professional Development Policy and Implementation Status of Elementary School Teachers in Taiwan and Mainland China - 劉鎮寧 Jen-Ning Liou; 吳子宏 Zai-Hong Wu; 邱世杰 Shi-Jie Qiu (National Changhua University of Education, 2015)
本研究針對臺灣與中國大陸小學教師專業發展的政策法規和實施現況進行探究，主要透過文件分析、焦點團體等研究方法的運用，並以高雄市和廣州市的國小教育人員為研究的主要對象，以期回應本研究的三個問題。首先，在專業發展政策法規上，本研究針對二者異同進行討論，分別歸納出四點相同與相異之處。其次，在教 師專業發展課程規劃方面，高雄市含括政策落實與學校自主二種類型；廣州市則是較偏向學校特色的發展。再次，在參與專業發展感受情形上，高雄市國小教師覺得可對專業發展課程進行選擇和決定，也認為專業學習社群的規劃能貼近教師的實際需求，至於對校內所辦理的進修課程，教師認為形式主義大於實質的效益。廣州市 的國小教師則是覺得因為分級制度，使得國小教師對研習課程有實際需求的必要，而且政府部門和學校相當重視在教學現場對教師的督導。最後綜合結論和建議以供當局參考。 This study investigated the professional development policy and implementation status of elementary school teachers in Taiwan and Mainland China. The subjects were elementary school teachers in Kaohsiung City and Guangzhou City. The research methods included document analysis and focus group, in order to answer the three research questions. First, regarding the laws and regulations of professional development policy, this study compared the similarities and differences between the two sides and respectively concluded four aspects of similarities and differences. Second, in regard to curriculum planning of teachers' professional development, Kaohsiung City gives considerations to both policy implementation and school autonomy, while Guangzhou City pays more attention to the development of significant features of schools. Third, regarding the perceptions of teachers participating in professional development, the elementary school teachers in Kaohsiung City think that they are allowed to select and determine the curriculum of professional development. They also think that the learning activities planned by the professional learning communities meet their practical needs, while the professional development courses provided on campus tend to put more emphasis on obeying formal rules than bringing about actual benefits. On the other hand, in the opinion of elementary school teachers in Guangzhou City, rating system makes it necessary that elementary school teachers have the actual demand for learning from the professional development courses. Moreover, they are conscious that government sectors and schools pay close attention to monitoring and supervising teachers in classroom settings. Finally, this study draws conclusions and offers some suggestions that may serve as references for the governing authorities.